Enhancing the cycle life of Li-S batteries by designing a free-standing cathode with excellent flexible, conductive, and catalytic properties - Lu, Q.; Sun, Y.; Liao, K.; Zou, X.; Hamada, I.; Zhou, W.; Ni, M.; Shao, Zongping (Pergamon, 2019)
Poor electrical conductivity of sulfur, sluggish redox kinetics, dissolution of intermediate polysulfides, and expansion in volume upon cycling are the main drawbacks that hamper the practical application of Li-S batteries. By taking advantages of the high conductivity and favorable catalytic activity of RuO2, we design a 3D carbon nanotube film with embedded RuO2 nanoparticles as a freestanding type of chemisorptive and catalyst-like cathode for Li-S batteries, which can be facilely prepared by a surfactant-assisted vacuum infiltration method. Both experimental and theoretical results reveal the excellent capability of RuO2 for anchoring polysulfides and accelerating the kinetics of polysulfides catalytic redox reactions. Besides, the 3D freestanding cathode is beneficial to overcoming pulverization during volume changes, especially for long-term cycling. At a high areal sulfur loading of 2 mg cm-2, favorable initial capacities of 750 and 1060 mA h g-1 respectively at 2 and 0.5 C are achieved. More attractively, the capacity after 1000 cycles maintains 405 mA h g-1 at 0.5 C with a loss in capacity of only 0.06% per cycle. Additionally, such freestanding cathode allows the batteries to be tested under various bending stages, hence encouraging more research works on fabrication of other 3D nanostructure families as high-performance cathodes for Li-S batteries.